A minimally invasive posterior lumbar interbody fusion for degenerative lumbar spine instabilities - Logroscino, C. A. (Springer-Verlag, 2011)
Percutaneous techniques may be helpful to reduce approach-related morbidity of conventional open surgery. The aim of the study was to evaluate the feasibility and safety of mini-open posterior lumbar interbody fusion for instabilities and degenerative disc diseases. From May 2005 until October 2008, 20 patients affected by monosegmental instability and disc herniation underwent mini-open lumbar interbody fusion combined with percutaneous pedicle screw fixation of the lumbar spine. Clinical outcome was assessed using the Visual Analog Scale, Oswestry Disability Index, and Short Form Health Survey-36. The mean follow-up was 24 months. The mean estimated blood loss was 126 ml; the mean length of stay was 5.3 days; the mean operative time was 171 min. At 24-month follow-up, the mean VAS score was 2.1, mean ODI was 27.1%, and mean SF-36 was 85.2%. 80 screws were implanted in 20 patients. 74 screws showed very good position, 5 screws acceptable, and 1 screw unacceptable. A solid fusion was achieved in 17 patients (85%). In our opinion, mini-open TLIF is a valid and safe treatment of lumbar instability and degenerative disc diseases in order to obtain faster return to daily activities.